Safety-critical trajectory tracking control for quadrotors - Li, Xinyi (Nanyang Technological University, 2022)
Safety-critical control is critical in the applications of unmanned aerial vehicles (UAVs). For instance, an aerial robot such as a quadrotor needs to realize fast collision-free flight. However, the navigation strategy may conflict with the safety requirement. In this dissertation, the problem of safety-critical trajectory tracking control for quadrotors is addressed. The proposed cascade controller consists of CLF-CBF-QP based position control, PID based velocity control and attitude control. In quadratic programming (QP), the hard safety constraints are derived from the Control Barrier Function (CBF) and the soft trajectory tracking constraints are formed based on a distance-based Control Lyapunov Function (CLF). The efficacy of the proposed approach is verified via simulations in MATLAB SIMULINK environment. The simulations include circular and square trajectories tracking with given ideal obstacles, and trajectory tracking with horizontal-range-limited LiDAR.